2014
DOI: 10.1152/ajpheart.00328.2014
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells are recruited in the infarcted mouse myocardium and may modulate fibroblast phenotype and function

Abstract: Regulatory T cells (Tregs) play a pivotal role in suppressing immune responses regulating behavior and gene expression in effector T cells, macrophages, and dendritic cells. Tregs infiltrate the infarcted myocardium; however, their role the inflammatory and reparative response after myocardial infarction remains poorly understood. We used FoxP3(EGFP) reporter mice to study Treg trafficking in the infarcted heart and examined the effects of Treg depletion on postinfarction remodeling using an anti-CD25 antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
150
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(156 citation statements)
references
References 38 publications
6
150
0
Order By: Relevance
“…Recently, another study has also reported that depletion of Tregs enhances the number of macrophages in myocardium. 54 Monocytic cells sorted from Treg-depleted mice showed significantly higher expression of inducible nitric oxide synthase 5 days post-MI when compared with cells sorted from control mice. Moreover, the expression of M2-associated anti-inflammatory cytokines IL-10 and transforming growth factor β1 was downregulated.…”
Section: Cd4mentioning
confidence: 90%
“…Recently, another study has also reported that depletion of Tregs enhances the number of macrophages in myocardium. 54 Monocytic cells sorted from Treg-depleted mice showed significantly higher expression of inducible nitric oxide synthase 5 days post-MI when compared with cells sorted from control mice. Moreover, the expression of M2-associated anti-inflammatory cytokines IL-10 and transforming growth factor β1 was downregulated.…”
Section: Cd4mentioning
confidence: 90%
“…Regulatory T cells are found in the cardiac tissue and play important roles in modulating immune responses (Saxena et al, 2014). Kuusisto et al (2012) demonstrated that CD3 + T cells were present in HCM patients, but were lacking in healthy subjects, suggesting that inflammation due to infiltrating immune cells is associated with HCM.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets have been suggested to be an important source of TGF-β1 in the pressureoverloaded myocardium (29); however, their role as a source of growth factors in the infarcted myocardium has not been systematically investigated. Lymphocyte subsets and mast cells infiltrate the infarcted heart (30)(31)(32)(33) and are capable of producing TGF-βs. Moreover, much like most tissues, the normal myocardium may contain constitutive stores of matrix-bound latent TGF-β that can be activated following injury (34), initiating a response even in the absence of de novo synthesis.…”
Section: Regulation Of Tgf-β Isoforms In Myocardial Infarctionmentioning
confidence: 99%
“…TGF-β also serves as a central mediator in T lymphocyte differentiation and activation, critically regulating phenotype and function of all subpopulations (69)(70)(71). Although activated subsets of T lymphocytes have been implicated in repair and remodeling of the infarcted heart (30,32,72), the relative role of TGF-β signaling in their recruitment and activation has not been investigated.…”
Section: Tgf-βmentioning
confidence: 99%